Early ovarian ageing. (18th March 2019) - Maclaran, Kate; Nikolaou, Dimitrios
Abstract : Key content: Early ovarian ageing (EOA) affects around 10% of women. Women with early ovarian ageing are frequently asymptomatic with normal fertility; however, continuing follicular loss will result in loss of fertility, menstrual irregularity and, finally, early menopause. As women increasingly delay childbirth, the physical, psychological and financial impact of EOA is escalating. Long‐term health effects include early menopause and increased cardiovascular risk. Improvements in the success of oocyte freezing have provided a treatment option when EOA is identified early. Learning objectives: To understand the prevalence and pathophysiology of EOA. To appreciate the effects of EOA on fertility, miscarriage risk and long‐term health. To be able to counsel women presenting with EOA regarding their fertility options. Ethical issues: Should women be screened for EOA? What is the efficacy of egg freezing for fertility preservation?